2013
DOI: 10.1016/j.ijpsycho.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Gritty people try harder: Grit and effort-related cardiac autonomic activity during an active coping challenge

Abstract: Grit, a recently proposed personality trait associated with persistence for long-range goals, predicts achievement in a wide range of important life outcomes. Using motivational intensity theory, the present research examined the physiological underpinnings of grit during an active coping task. Forty young adults completed the Short Grit Scale and worked on a self-paced mental effort task. Effort-related autonomic nervous system (ANS) activity was assessed using impedance cardiography, which yielded measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 55 publications
8
58
0
5
Order By: Relevance
“…Although previous research has found that the two different facets of grit correspond differently to behaviour (see Silvia et al, 2013), a betweensubjects ANOVA yielded similar differences among groups both on the Perseverance of Effort, F(2, 138) = 5.17, p = .007, g 2 p = 0.25, and Consistency of Interest subscales, F(2, 138) = 4.69, p = .011, g 2 p = 0.17), with similar least squares difference test results across groups. Similar to the findings reported by Duckworth and Quinn (2009), the two subscales were highly correlated in our sample (r = .41, p < .001), though our sample scored significantly higher on the Perseverance of Effort subscale (M = 1.88, SD = 0.35) than the Consistency of Interest subscale, M = 1.51, SD = 0.33 t(140) = 11.75, p < .011.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although previous research has found that the two different facets of grit correspond differently to behaviour (see Silvia et al, 2013), a betweensubjects ANOVA yielded similar differences among groups both on the Perseverance of Effort, F(2, 138) = 5.17, p = .007, g 2 p = 0.25, and Consistency of Interest subscales, F(2, 138) = 4.69, p = .011, g 2 p = 0.17), with similar least squares difference test results across groups. Similar to the findings reported by Duckworth and Quinn (2009), the two subscales were highly correlated in our sample (r = .41, p < .001), though our sample scored significantly higher on the Perseverance of Effort subscale (M = 1.88, SD = 0.35) than the Consistency of Interest subscale, M = 1.51, SD = 0.33 t(140) = 11.75, p < .011.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Duckworth and Quinn (2009) found that Consistency of Interest was strongly predictive of career consistency, whereas Perseverance was predictive of GPA. Furthermore, recent work in regards to psychophysiological measures found that greater physiological expenditure was positively correlated with scores on the Perseverance of Effort subscale, whereas these measures were negatively correlated with the Consistency of Interest subscale (Silvia, Eddington, Beaty, Nusbaum, & Kwapil, 2013).…”
mentioning
confidence: 97%
“…This task is challenging because ignoring centrally-presented words is hard and making parity judgments is unusual (Aquino & Arnell, 2007; Harris & Pashler, 2004). This task has been effective in our past research (Silvia, Eddington, Beaty, Nusbaum, & Kwapil, 2013; Silvia & Phillips, 2013). …”
Section: Methodsmentioning
confidence: 94%
“…As in our past work (Silvia, Eddington et al, 2013), the parity task was “unfixed” in difficulty (Wright et al, 2002). Each trial remained on the screen until people responded and then terminated immediately, so people could work at their own pace.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated that individuals who score highly on measures of grit, and who persevere in the face of difficult tasks, are often more successful in a variety of domains including health, education, and finances [20,22,23,35,36]. It remained unclear whether grittier individuals persist because they believe there are more likely/larger rewards available in the environment than do individuals with less grit, or if instead gritty and non-gritty individuals both make similar inferences regarding what rewards are available in the environment, but gritty individuals infer that they are more likely to actually reach those rewards.…”
Section: Discussionmentioning
confidence: 99%